2021
DOI: 10.1021/acscatal.1c01515
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Catalytic Hydrogenolysis of Chlorosilanes into Hydrosilanes with Superbases

Abstract: The efficient synthesis of hydrosilanes by catalytic hydrogenolysis of chlorosilanes is described, using an iridium (III) pincer catalyst. A careful selection of a nitrogen base (incl. sterically hindered guanidines and phosphazenes) can unlock the preparation of Me3SiH, Et3SiH and Me2SiHCl in high yield (up to 98%), directly from their corresponding chlorosilanes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…Finally, only traces of hydrosilane could be detected in the hydrogenolysis of Me 3 SiCl (Table 3, entry 8). These findings are consistent with the trends obtained using organometallic catalysts for the hydrogenolysis of (pseudo)halosilanes, pointing to a more difficult cleavage of the Si−Cl bond [7c,e] …”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, only traces of hydrosilane could be detected in the hydrogenolysis of Me 3 SiCl (Table 3, entry 8). These findings are consistent with the trends obtained using organometallic catalysts for the hydrogenolysis of (pseudo)halosilanes, pointing to a more difficult cleavage of the Si−Cl bond [7c,e] …”
Section: Methodssupporting
confidence: 90%
“…Mechanistic investigations derived from the iridium and ruthenium catalyzed hydrogenolysis of Si−X bonds have shown that the generation of a metal hydride from H 2 is key to yield a hydrosilane by hydride transfer to the silicon atom [7c–e] . To perform this transformation without a metal, we have sought to use borohydrides as hydrogen transfer reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, hydrosilane synthesis strategies rely on energy-intensive processes which involve strong reducing agents such as LiAlH 4 . Hydrogenolysis of Si–X bonds has been introduced by the groups of Hidai, , Shimada, , Schneider, and Cantat as an alternative way to hydrosilanes and would be a convenient approach when using green H 2 generated via both electrochemical and photochemical splitting of water (Scheme ). , Due to the paucity of work in this area, the development of novel systems favoring Si–X to Si–H conversion is crucial, and their studies should give a better understanding of the intrinsic mechanism of such transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The Schneider’s group also reported in 2018 excellent conversion and yields in Me 3 SiH, Me 2 SiH 2 , or Me 2 SiH­(OTf) from the corresponding triflates when catalyzed with ruthenium­(II) pincer complex C (Scheme ). Finally, our group recently reported the use of the iridium­(III) pincer [( t Bu POCOP)­IrHCl] ( 1 ) as an efficient catalyst in the hydrogenolysis of [Si]–Cl compounds when combined with superbases such as BTPP (BTPP = ( t Bu-imino)­tri­(pyrrolidino)­phosphorane) …”
Section: Introductionmentioning
confidence: 99%